Paying More for Less: Why Don't Households in Tanzania Take Advantage of Bulk Discounts?. (10th January 2020) - Dillon, Brian; De Weerdt, Joachim; O'Donoghue, Ted
Abstract: Do poor households shop in a way that leaves money on the table? A simple way to maximize consumption, conditional on available cash, is to avoid regularly purchasing small amounts of nonperishable goods when bulk discounts are available at modestly larger quantities. Using two-week transaction diaries covering 48, 501 purchases by 1, 493 households in Tanzania, this article finds that through bulk purchasing the average household could spend 8.7 percent less without reducing purchasing quantities. Several explanations for this pattern are investigated, and the most likely mechanisms are found to be worries about over-consumption of stocks and avoidance of social taxation. Contrary to prior work, there is little indication that liquidity constraints prevent poorer households in the sample from buying in bulk, possibly because the bulk quantities under examination are not very large.